2022
DOI: 10.3390/ijerph19031856
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Volatile Organic Compounds from Dried Common Rush (Juncus effusus L. var. decipiens Buchen.) on Humans

Abstract: This study compared the participants’ physiological responses and subjective evaluations of air scented with different concentrations of common rush (Juncus effusus L. var. decipiens Buchen.) (30 g and 15 g, with fresh air as a control). We asked 20 participants to complete a series of visual discrimination tasks while inhaling two different air samples. We evaluated (1) brain activity, (2) autonomic nervous activity, and (3) blood pressure and pulse rate, (4) in combination with self-evaluation. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…For aroma stimulation, essential oils were diffused in the room using an aroma diffuser (ESSWNTIAL OIL DIFFUSER aromore TL -EOD -A1, TREE OF LIFE Co., Ltd., Japan). Based on previous research on aromatherapy with essential oils [33] , the diffuser was positioned at a distance of approximately 1 m from the participant's nostrils, and the stimulation began just before the 10-min resting period in a sitting position before aerobic exercise. Lavender essential oil (Lavender France, TREE OF LIFE Co., Ltd., Japan) was used in the aroma condition, whereas distilled water (Distilled water CAS RN:7732-18 − 5, Hayashi Pure Chemical Ind., Ltd., Japan) was used in the placebo condition.…”
Section: Aroma Stimulationmentioning
confidence: 99%
“…For aroma stimulation, essential oils were diffused in the room using an aroma diffuser (ESSWNTIAL OIL DIFFUSER aromore TL -EOD -A1, TREE OF LIFE Co., Ltd., Japan). Based on previous research on aromatherapy with essential oils [33] , the diffuser was positioned at a distance of approximately 1 m from the participant's nostrils, and the stimulation began just before the 10-min resting period in a sitting position before aerobic exercise. Lavender essential oil (Lavender France, TREE OF LIFE Co., Ltd., Japan) was used in the aroma condition, whereas distilled water (Distilled water CAS RN:7732-18 − 5, Hayashi Pure Chemical Ind., Ltd., Japan) was used in the placebo condition.…”
Section: Aroma Stimulationmentioning
confidence: 99%
“…To investigate the effects of the tatami mat scent, Sun et al evaluated the effect of the scent of volatile organic compounds (VOCs) from Juncus effusus L. var. decipiens Buchen, dried igusa, and found an increase in alpha waves when subjects smelled the scent 3 . As the alpha band amplitude can be an indicator of the change in arousal level, this study showed that the scent of dried igusa has the effect of awakening the brain 4,5,6 .…”
Section: Introductionmentioning
confidence: 99%